Fine mapping and target gene identification of qSE4, a QTL for stigma exsertion rate in rice (Oryza sativa L.) - Guo, Naihui; Wang, Yakun; Chen, Wei; Tang, Shengjia; An, Ruihu; Wei, Xiangjin; Hu, Shikai; Tang, Shaoqing; Shao, Gaoneng; Jiao, Guiai; Xie, Lihong; Wang, Ling; et al. (Frontiers in Plant Science, 2022)
The stigma exsertion rate (SER) is a complex agronomy phenotype controlled by multiple genes and climate and a key trait affecting the efficiency of hybrid rice seed production. Using a japonica two-line male sterile line (DaS) with a high SER as the donor and a tropical japonica rice (D50) with a low SER as the acceptor to construct a near-isogenic line (NIL (qSE4DaS)). Populations were segregated into 2143 individuals of BC3F2 and BC4F2, and the stigma exsertion quantitative trait locus (QTL) qSE4 was determined to be located within 410.4 Kb between markers RM17157 and RM17227 on chromosome 4. Bioinformatic analysis revealed 13 candidate genes in this region. Sequencing and haplotype analysis indicated that the promoter region of LOC_Os04g43910 (ARF10) had a one-base substitution between the two parents. Further Reverse Transcription-Polymerase Chain Reaction (RT-PCR) analysis showed that the expression level of ARF10 in DaS was significantly higher than in D50. After knocking out ARF10 in the DaS background, it was found that the SER of arf10 (the total SER of the arf10-1 and the arf10-2 were 62.54% and 66.68%, respectively) was significantly lower than that of the wild type (the total SER was 80.97%). Transcriptome and hormone assay analysis showed that arf10 had significantly higher auxin synthesis genes and contents than the wild type and the expression of auxin signaling-related genes was significantly different, Similar results were observed for abscisic acid and jasmonic acid. These results indicate that LOC_Os04g43910 is mostly likely the target gene of qSE4, and the study of its gene function is of great significance for understanding the molecular mechanisms of SER and improving the efficiency of hybrid seed production.